REVIEW OF THE PROVISION OF TAX FACILITIES IN MANAGEMENT OF MSMEs IN THE TIME OF THE COVID-19 PANDEMIC - Rakhmayudhi Rakhmayudhi; Titin Kartini (INFOKUM, 2022)
To maintain stability in economic growth and people's purchasing power, as well as productivity in the business sector, the government has issued several policy instruments in the taxation sector. This thesis discusses the review of the provision of tax facilities in the context of handling the Covid-19 pandemic for the Micro, Small and Medium Enterprises (MSME) sector. The purpose and use of this research is to find out the form of tax facilities in the context of handling the Covid-19 pandemic for the MSME sector, how to provide these tax facilities and also to find out the obstacles in the implementation and implementation of the provision of tax facilities. The method used in this research is normative juridical, namely an approach that emphasizes the law which is conceptualized as what is written in the legislation, with regard to the subject matter to be discussed in relation to practice in the field so that it can solve a problem by collecting data and analyzing . The results of the study can be concluded that the form of tax facilities provided by the government in the context of handling the Covid-19 pandemic for the MSME sector is in the form of Final PPh borne by the Government. This means that the income received by the MSME actors is not calculated as income that is subject to tax. However, there are still many MSME actors who have not taken advantage of the tax facilities provided by the government. This is due to the lack of socialization carried out by the government, and the low level of tax literacy in the community. In addition, to be able to take advantage of this tax facility is still difficult for MSME actors because most of the administrative processes are carried out online, where MSME actors are still accustomed to fulfilling their tax obligations manually. As a suggestion, DGT is expected to cooperate with several strategic partners in conducting socialization and training on the implementation of procedures for utilizing tax incentive facilities..